Double-Face Meets the Bacterial World: The Opportunistic Pathogen Stenotrophomonas maltophilia - Lira, Felipe; Berg, Gabriele; Martínez, José L. (Frontiers in Microbiology, 2017)
Most studies on bacterial virulence focus on the pathogen itself. However, it is important to recall that the in-host behavior and the virulence of bacterial pathogens constitute a complex situation that depends on both the microorganisms and the infected host. While healthy people (the community) is infected by classical pathogenic microorganisms, able to cope with the anti-infection defenses of the host, in the case of people with basal diseases, debilitated or immunodepressed, the range of pathogens able to cause infection is wider and includes the so-named opportunistic pathogens, which lack the inherent ability to cause disease in healthy hosts and rarely produce infections in the community. Some of the most relevant opportunistic pathogens, as Stenotrophomonas maltophilia, have an environmental origin and, in occasions present interesting biotechnological properties. Consequently, it is important knowing whether S. maltophilia isolates recovered from infections constitute a specific phylogenetic branch that has evolved towards acquiring a virulent phenotype as it happens in the case of classical pathogens or rather, any member of this bacterial species is capable of producing infection and its pathogenic behavior is mainly a consequence of the host situation. To address this question, we analyzed a set of environmental and clinical S. maltophilia strains. Our results indicate that this opportunistic pathogen presents a large core genome and that the distribution of genes in general and of known virulence determinants in particular, is similar among environmental and clinical isolates. The majority of genes not belonging to the S. maltophilia core genome are present in just one or two of the analyzed strains. This indicates that, more than speciation into different lineages (virulent and environmental), the evolution of S. maltophilia is based in the strain-specific acquisition of genes, likely involved in the adaptation of this bacterial species to different microniches. In addition, both environmental and clinical isolates present low susceptibility to several antimicrobials. Altogether our results support that S. maltophilia does not present a specific evolutionary branch towards virulence and most likely infection is mainly the consequence of the impaired anti-infective response of the infected patients.